GE_GERICHTE A/2822/2024 vom 12. Juni 2025 - GE Cour de justice (2025)
NOTIFICATION IRRÉGULIÈRE;VALEUR LIMITE D'EXPOSITION;ASSAINISSEMENT(EN GÉNÉRAL);PERTURBATEUR PAR COMPORTEMENT | LPA.47; LPE.7.al1; LPE.7.al7; LPE.25.al1; OPB.7.al1.letb; LPE.15; LPE.16